Instruments to evaluate argumentative text of university students - Gonzales R., María (2014)
The present work is a qualitative and explorer study. Its objective is to propose criteria for the evaluation of the writing production of argumentative texts of university students in the first term. Two hypotheses are formulated in this research. The first one, younger students have the cognitive scheme of oral discussion and, therefore they know the act sequence of such communicative event because of their experiences in oral daily practices to convince other ones, but such acts are evidently different from those specialized ones of scientific discourse which are argumentative and written. For that reason, and this is the second hypothesis, it is necessary to activate their previous knowledge about discussion practice in oral dynamics to ensure the success in the production of an argumentative writing with cohesive propositions. The result of this exploratory study is a cognitive linguistic textual discursive instrument that evaluates argumentative abilities of students to plan, in the future, an argumentation teaching program.